Vested Interests in a Positive Theory of Stagnation and Growth - Krusell, Per; Rios-Rull, Jose-Victor (Review of Economic Studies, 1996)
We study a positive theory of stagnation and growth aimed at understanding the large variations in growth outcomes across actual economies. The theory points to the fundamental role played by vested interests in determining policies which are key to the growth process: some agents seek to prevent the adoption of new technologies. We develop a model of technology adoption, and show how technological innovation may sow the seeds of its own destruction. In particular, we find that the equilibrium is characterized by a long cycle of stagnation and growth. Over this cycle, incumbent innovators have sufficient political influence that new technologies are prohibited, and only as these incumbents are phased out of the economy will new innovation occur. In formalizing our theory we make a methodological contribution by characterizing dynamic voting equilibria in which voters must forecast the effects of different current policies on future prices and policy outcomes.